2018
DOI: 10.1371/journal.pone.0204170
|View full text |Cite
|
Sign up to set email alerts
|

GPx3-mediated redox signaling arrests the cell cycle and acts as a tumor suppressor in lung cancer cell lines

Abstract: Glutathione peroxidase 3 (GPx3), a major scavenger of reactive oxygen species (ROS) in plasma, acts as a redox signal modulator. However, the mechanism underlying GPx3-mediated suppression of cancer cell growth is unclear. The aim of this study was to identify these mechanisms with respect to lung cancer. To enhance the redox modulating properties of GPx3, lung cancer cells were subjected to serum starvation for 12 h, resulting in ROS generation in the absence of oxidant treatment. We then investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Interestingly, and in accordance t our ndings, reduced expression of GPX3 has been shown to be linked to increased proliferation rate in NSCLC by modulating redox mediated signals [105]. Further, GPX2 is associated with invasion, metastasis and tumor growth, as GPX2 knock down reduced levels of EMT markers such as vimentin, SNAI1 and MMP2 [106].…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, and in accordance t our ndings, reduced expression of GPX3 has been shown to be linked to increased proliferation rate in NSCLC by modulating redox mediated signals [105]. Further, GPX2 is associated with invasion, metastasis and tumor growth, as GPX2 knock down reduced levels of EMT markers such as vimentin, SNAI1 and MMP2 [106].…”
Section: Discussionsupporting
confidence: 85%
“…Lower levels of GPX3, SELENOW, SELENOK, SELENBP1 and SECISBP2 in lung adenocarcinoma were associated with poor survival, while high levels of GPX3 in lung squamous cell carcinoma were associated with poor survival, possibly related to EMT activation. Recently, it was shown that GPX3 can inhibit the proliferation of lung cancer cells ( 49 ), and GPX3 levels, which can be regulated by methylation, were lower in lung cancer patients ( 50 , 51 ). In this study, hypermethylation of GPX3 can inhibit GPX3 expression in lung adenocarcinoma, while there was no difference in methylation between lung squamous cell carcinoma and normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, antioxidant enzymes, including the GPx family members, are important regulators of these signaling cascades by manipulating levels of oxidants at cellular redox signaling hubs [28,85]. We highlight several studies in Section 3.2 where GPx3 has been implicated in modulating the activity of redox signaling pathways in cancer cells [32,[86][87][88][89][90].…”
Section: Disease Association With Aberrant Gpx3mentioning
confidence: 99%
“…Gene hypermethylation Poor patient outcome, potential biomarker [125] Inhibit activation of Erk-NF-κB-cyclin B1 pathway [86] Melanoma Gene hypermethylation Cancer progression, poor patient outcome [111] Inhibit expression of hypoxia-inducible factors 1α and 2α [89] [116] Myeloid leukemia N/D Cancer progression, poor patient outcome [116,129] Ovarian cancer N/D Cancer cell survival under anchorage independence and oxidative stress [14] Ovarian clear cell adenocarcinoma N/D Chemoresistance [130] As summarized in Table 1, several studies have reported a decrease or loss of GPx3 expression in tumor tissues [61][62][63]86,87,[109][110][111][112][113][114][115]. In many of these cancers, downregulation of GPx3 parallels cancer progression, and is often associated with poor patient outcome [62,90,109,110,123].…”
Section: Altered Gpx3 Expression and Role In Tumor Tissuesmentioning
confidence: 99%